100% Success in Motivation: Ideal Education or Just Creative Pedagogy? - Andrei Aleinikov; Anny Mavambu Ndulu (Journal of Educational Issues, 2024)
This article tackles the keystone of any successful education, regardless of the subject, program, school, level of education, age of the learner, etc. Millions of educators, education administrators, and even parents would like to know how to make their educational process and child rearing efforts successful. Finally, the solution is addressed here. The secret of the most effective—100% successful—teaching methodology is uncovered. The article consists of two parts: the first is general, it re-emphasizes the classical approach to ideas related to motivation, and available in literature. The second is specific and scripted in the form of an interview. It discloses the secrets of Creative Pedagogy, famous for its unbelievable rate of success proven at all levels of education. Warning: unlike traditional research papers, this article adopted a hybrid written style combining a narration with a live discussion (a dialog). We welcome readers to participate in our dialog!